A new species of Wyeomyia (Diptera: Culicidae) from Heliconia flower bracts in northern South America - Ribeiro, Paulino Siqueira; Pavan, Márcio Galvão; Da Silva, Marcos Barbosa; Galvão, Cleber; Lourenço-De-Oliveira, Ricardo; Motta, Monique Albuquerque (Zootaxa, 2021)
A new species of the genus Wyeomyia, Wyeomyia (Decamyia) anthica sp. n., is described based on morphological and molecular analyses and is illustrated in larval, pupal and adult life stages. Among the four valid species of the subgenus Decamyia, the new species is closest to Wy. ulocoma (Theobald, 1903), from which it can be distinguished by morphological characters of the male genitalia, larval and pupal stages, and mitochondrial cytochrome c oxidase 1 gene sequence. Wyeomyia ulocoma is recorded from Brazil for the first time.